Idade de entrada internacional, velocidade de internacionalização e seus efeitos sobre o crescimento no exterior de pequenas e médias empresas - Carvalho, Selma (2009)
Using quantitative analysis, this dissertation aimed to measure and analyze the relationships among international age, internationalization speed and international growth of brazilian small and medium size enterprises (SMEs). A sample of exporting and industrial SMEs from Sao Paulo was used to calculate these relationships. The results show that the international age is a moderating force, with a negative influence on the positive relationship between internationalization speed and their growth in international markets. Summing up, the results show that ‘younger’ firms, which started to internationalize their activities at an earlier phase of their lives, grew more than those firms that did so when they were more ‘mature’. This finding indicates that, despite ‘mature’ SMEs consolidate their capacities in domestic markets over the years, ‘younger’ ones seem to be better adapted to go abroad, at least on this phase of their internalization process. Another finding of this dissertation confirms that relationship in a domestic market characterized by fierce competition due to the presence of industrial multinational companies subsidiaries, as it is the case of Sao Paulo, younger firms that have been successful in expanding abroad faster and in growing more that their counterparts have been using multiple ways to access international markets.